“Is It Bad I Don’t Know this Yet?”: At-Promise College Students, Financial Aid Knowledge, and Retention (Higher Education Politics and Economics, 2025)
This study describes how at-risk students articulate their knowledge of federal financial aid policy during COVID-19. We interviewed 14 students who were on financial aid warning, a status defined by federal financial aid policy regulations, to examine what students understand about their financial aid standing and the criteria to keep their funding. Findings suggest students were often confused about financial aid eligibility criteria, even though they confidently expressed incorrect information about financial aid policies. Moreover, students were uncertain about how to connect with institutional financial aid resources and did not understand that financial aid advising extended beyond their first semester. This study fills multiple gaps in the literature and articulates how institutions can improve students’ understanding of financial aid policy through multiple modes of communication, intentional interventions, and clearer policies. Implications for research, policy, and practice are addressed.